Speckle correlation method used to measure object's in-plane velocity - Smíd, Petr; Horváth, Pavel; Hrabovský, Miroslav (Applied optics, 2007)
We present a measurement of an object's in-plane velocity in one direction by the use of the speckle correlation method. Numerical correlations of speckle patterns recorded periodically during motion of the object under investigation give information used to evaluate the object's in-plane velocity. The proposed optical setup uses a detection plane in the image field and enables one to detect the object's velocity within the interval (10-150) microm x s(-1). Simulation analysis shows a way of controlling the measuring range. The presented theory, simulation analysis, and setup are verified through an experiment of measurement of the velocity profile of an object.
Keywords: Physics; pohyb těles; optika a fotonika; Image Processing, Computer-Assisted; Lasers; počítačové zpracování obrazu; statistické modely; Motion; teoretické modely; Time Factors; lasery; design vybavení; fyzika; Equipment Design; Models, Statistical; Models, Theoretical; kovy; Optics and Photonics; časové faktory; mikroskopie; Metals; Microscopy